Pengaruh Kreativitas Guru dan Motivasi Belajar Terhadap Hasil Belajar Siswa di SD Katolik ST. Nicolaus Talawaan - Salindeho, Cicilia Anastasia; Tamboto, Fabyana Imelda; Mangundap, Jelvi Monica (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
The low quality of education is one of the problems that continues to be sought for solutions. This is caused by a lack of student motivation to learn and results in low learning outcomes. The learning outcomes of these students are an indicator of the high and low quality of education in a region. Improving the quality of education in elementary schools must pay attention to character education, ethics, morals and manners. Many factors influence educational success and one of the most determining factors is the teacher. Teachers must be creative in creating a learning environment that supports the success of the learning process at school. Teachers must be able to motivate students to actively learn and be able to create innovations so that the learning process becomes more enjoyable by applying various different media, models and methods. This research aims to determine the influence of teacher creativity and learning motivation at SD St. Nikolaus Talawaan, North Minahasa Regency.